Complex Adaptive Systems, Agent-Based Modeling and Information Assurance - Burns, A (2012)
Management of information security issues can be viewed as a complex adaptive system in that hackers are constantly developing new means of trying to penetrate security systems and access information assets. Organizational must adapt too these threats by updating security procedures and systems and by training employees in what must be done to counteract new threats. We present agent-based models that illustrate “phishing” problems, and General Deterrence Theory and Protection Motivation Theory and their application to IA problems. These models are written in Netlogo, an open-source agent-based modeling system, and are freely available for education and training in IA